Mitteilungen aus der Arbeitsgemeinschaft Evidenzbasierte Medizin der AGMB - von Gernler, Marc; Krause, Evamaria; Cascant Ortolano, Lorena (GMS Medizin – Bibliothek – Information, 2024)
The working group Evidence-Based Medicine (AG-EBM) of the German Medical Library Association (AGMB) celebrates its fifth anniversary in 2024. It continues its work in the years 2023 and 2024 in the form of virtual meetings. The group meeting of the AG-EBM at the annual conference of the AGMB 2024 in Mainz provides an opportunity to get in touch with the group and its members.